1996
DOI: 10.1063/1.1146585
|View full text |Cite
|
Sign up to set email alerts
|

A linear electric motor to study turbulent hydrodynamics

Abstract: A linear electric motor has been built to study hydrodynamic instabilities at the interface between fluids subjected to acceleration. The facility is powered by 16 independent capacitor banks to provide arbitrary acceleration profiles up to 1000 times earth’s gravity. Electrical measurements include the current, magnetic field, acceleration, and projectile trajectory. The instability is observed with flash shadowgraphy. The shot turnaround time is <15 min and over 100 shots can be taken before replacing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Later, Dimonte & Schneider (2000) found bubbles and spike responses of θ b = 0.25 and θ s = 0.3 (for A ∼ 0.7). However, to compensate for demixing caused by any residual deceleration in their linear electric motor system (Dimonte et al 1996), it was suggested that these exponents may have to be increased by ∼10 %. Experiments performed using membranes by Prasad et al (2000) produced a late-time growth exponent of (0.26 ≤ θ ≤ 0.33).…”
Section: Mixing Widths and Scalingmentioning
confidence: 99%
“…Later, Dimonte & Schneider (2000) found bubbles and spike responses of θ b = 0.25 and θ s = 0.3 (for A ∼ 0.7). However, to compensate for demixing caused by any residual deceleration in their linear electric motor system (Dimonte et al 1996), it was suggested that these exponents may have to be increased by ∼10 %. Experiments performed using membranes by Prasad et al (2000) produced a late-time growth exponent of (0.26 ≤ θ ≤ 0.33).…”
Section: Mixing Widths and Scalingmentioning
confidence: 99%
“…Here, we conduct experiments on the Linear Electric Motor (LEM) [13] using different acceleration profiles to measure the critical wavelength l c and amplitude P cr , and to compare 2D and 3D perturbations. The elastic material is chosen to be yogurt because its constitutive properties ͑m, h, s 0 ͒ are well characterized [14] and satisfy Eqs.…”
mentioning
confidence: 99%
“…Once the flow becomes self‐similar, the growth of the instability is described by the power law and the corresponding coefficient θ . Numerical and experimental investigations suggested slightly different values for θ . The discrepancies in the estimation between the experiments and the numerical simulations are mainly due to the different perturbation wavelengths .…”
Section: Sources Of Uncertaintymentioning
confidence: 77%
“…Numerical and experimental investigations suggested slightly different values for . 33,35,35,67,[69][70][71] The discrepancies in the estimation between the experiments and the numerical simulations are mainly due to the different perturbation wavelengths. 72 Furthermore, the power law coefficient is correlated with the density ratio of the 2 fluids.…”
Section: Sources Of Uncertaintymentioning
confidence: 98%